Recommendations for under-represented entrepreneurship. Issue 1 (31st May 2019) - Pathak, Saurav
Abstract : Purpose: The purpose of this study is to make strategic recommendations that benefit under-represented entrepreneurship (UE). Design/methodology/approach: The approach toward suggesting the proposed strategic recommendations is conceptual in nature. Blumberg's theory of nested level of resource structure and McPherson's theory of homophily will be invoked. Findings: Under-represented entrepreneurship would benefit from initiating key resource identification and acquisition at a meso-level, i.e. within one's own community in the first place and engaging in community-based collaborative and collective entrepreneurship. Research limitations/implications: The proposed strategies have not been validated empirically. Originality/value: The beneficial effects of implementing these strategies for UE will be felt in stages. First, communities will emerge as entrepreneurial as a whole. Subsequently, societal-level attribution of these communities as "entrepreneurial communities" will occur providing the necessary visibility and acceptance they would need to participate, contribute and get blended with more traditional entrepreneurship without distinction or prejudice.